The trend of physical education teachers in middle schools towards the values of belonging -A field study in some sample middle schools in M'sila province- - saidai achour,; dechicha amine,; legoui walid, (sports creativity, 2025)
The objective of this study was to identify the direction of the teachers of physical education and sports in the intermediate education stage towards the values of belonging. In order to achieve the objectives of the study, the researcher used the descriptive descriptive method and applied the trend scale towards belonging to researcher Latifa Khader Ibrahim (2000). Study on a sample composed of 170 teachers of physical education and sports averages of the state of Mesila, and the results of the study that: - There is a positive trend among the teachers of physical education and sports in the middle education towards the values of belonging résumé : L'objectif de cette étude était d'identifier l'orientation des enseignants d'éducation physique et sportive au stade de l'enseignement intermédiaire vers les valeurs d'appartenance.Pour atteindre les objectifs de l'étude, le chercheur a utilisé la méthode descriptive descriptive et appliqué l'échelle de tendance à l'appartenance à la chercheuse Latifa Khader Ibrahim (2000). Étude sur un échantillon composé de 170 enseignants en éducation physique et sportive, moyennes de la Wilaya de M'sila , et résultats de l'étude qui : - Les enseignants en éducation physique et sportive de l'enseignement moyen ont tendance à adopter les valeurs d'appartenance